Preoperative Endovascular Embolization of Intracranial Hemangioma: A Case Report - Gilbert Tangkudung; Jeffry Foraldy; Yovanka Manuhutu (Universitas Airlangga, 2023)
Highlight: Preoperative tumor embolization was performed to reduce intraoperative risk and maximize resection success Endovascular embolization has developed into an important and effective adjuvant in tumor management before a surgical resection. ABSTRACT Introduction: Hypervascular tumors of the head, neck, and central nervous system are associated with a high risk of bleeding during surgery. Hemangioma is a benign neoplasm that tends to grow rapidly, bleed, and have a high recurrence rate, especially after partial resection. Considering that hemangioma is a type of tumor with high vascularity, preoperative tumor embolization was performed to reduce intraoperative risk and maximize resection success. Case: A 33-year-old female came with the chief complaint of chronic progressive headaches and vision loss in the last 5 years. She got a lump on her forehead and had a visual acuity of 1/∞ in both eyes. She had already been diagnosed with hemangioma at a secondary regional hospital, where she bled profusely on the operating table, causing the resection to be discontinued. She was referred to our hospital for preoperative embolization. She underwent an endovascular embolization procedure with PVA particles to seal the feeder artery to the tumor. After embolization, angiography showed a complete devascularized tumor lesion. A total resection was done three days later with minimal bleeding compared to the first surgery. After a three-month follow-up, there was no new neurological deficit, and her headache was resolved completely, although her vision still did not improve. Conclusion: Endovascular embolization has developed into an important and effective adjuvant in tumor management before a surgical resection. Advances in catheter-based techniques, in conjunction with the development of the neurointervention field, are expected to raise the number of perioperative embolization procedures performed.